Restorative Justice in the KUHP and Protection of Sexual Violence Victims - Jovansyah Mulya Cipta Wibawa; Rangga Jayanuarto; Sinung Mufti Hangabei; Hendi Sastra Putra (Fakultas Syariah INSURI Ponorogo, 2025)
The revision of Indonesia's Criminal Code (KUHP) introduces restorative justice as a mandatory consideration in sentencing, requiring judges to evaluate forgiveness from victims or their families as part of the sentencing process. This study examines the implications of this provision when applied to sexual violence cases, particularly in relation to the Sexual Violence Crime Law (UU TPKS), which expressly prohibits non-judicial settlement as a form of victim protection. Using a normative legal research method supported by statute, conceptual, and case approaches, this article analyzes the interaction between the KUHP and the UU TPKS, alongside documented cases where victims experienced pressure to accept restorative agreements. Drawing on victimology and feminist legal theory, the study highlights the risk of revictimization, unequal bargaining power, and reinforcement of patriarchal structures when restorative justice is used in sexual violence cases. Findings show that applying restorative mechanisms to such cases creates legal uncertainty and contradicts the protective mandate of the UU TPKS. This article argues that restorative justice must be normatively limited and not applied to sexual violence. Clear regulatory harmonization and trauma-informed implementation guidelines are necessary to ensure a victim-centered approach to justice when the new KUHP becomes fully enforceable.